Praktek Pemenuhan Hak Nafkah Anak Pasca Perceraian Oleh Ibu Menurut Q.S. Al-Baqarah Ayat 233 (Studi Di Pondok Pesantren Al-Mahrusiyah III Ngampel Kota Kediri) - Rizki, Rieza; Al Amin, Habibi (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2023)
Divorce is one of the things that results in the breakdown of the marriage relationship. This also has an impact on children born in the marriage. The obligation to fulfill children's maintenance rights is basically still the father's obligation, based on one of the editorials of Q.S. al-Baqarah verse 233 which states that the obligation to provide maintenance is the father's obligation. However, there are cases where after divorce the fulfillment of children's maintenance rights is carried out entirely by the mother. This study focuses on 1) the fulfillment of children's maintenance rights according to Q.S. al-Baqarah verse 233 and 2) the fulfillment of children's maintenance rights after divorce by the mother according to Q.S. al-Baqarah verse 233. This study is a literature study with qualitative methods. The case data in this study was found in other research that the author did before. The conclusions of this study are 1) the fulfillment of child maintenance rights according to Q.S. al-Baqarah must be carried out based on the needs and best interests of the child and 2) the practice of fulfilling child maintenance rights after divorce by the mother is in line with the content of Q.S. al-Baqarah verse 233 because the division of duties in the verse cannot be interpreted rigidly and the implementation of child maintenance must pay attention to the needs and best interests of the child.